SINERGI DAKWAH KONTEMPORER, KURIKULUM MERDEKA DAN AI DALAM TRANSFORMASI PENDIDIKAN ISLAM - Muna; Muhammad Fauzan Aziman (PT. Sulthan Journal Publisher, 2026)
This study aims to examine the role of contemporary da'wah and the implementation of the Merdeka Curriculum in developing adaptive Islamic education management in the era of Artificial Intelligence (AI). Using a qualitative-conceptual approach with the library research method, this study analyzes how Islamic educational institutions can integrate traditional values with modern technology. The findings indicate that the Merdeka Curriculum, through the P5 RA (Strengthening the Pancasila and Rahmatan Lil Alamin Student Profile Project), provides a strategic framework for religious moderation and character building. Furthermore, the integration of AI acts as a catalyst for personalized learning and digital da'wah, although it faces challenges such as infrastructure gaps and digital ethics (adab). This research concludes that a synergy between flexible curriculum management, teacher digital competency, and AI ethics reconstruction is essential for the future relevance of Islamic education